WORKING CAPITAL MANAGEMENT AMONG LISTED COMPANIES OF PAKISTAN - ul-Hassan, Waqar; Zubair, Mohsin; Hasnain, Zeeshan; Hussain, Shahbaz (International Journal of Research -GRANTHAALAYAH, 2017)
The study aims to investigate the strength of working capital management for measuring the financial performance of listed stocks. The study incorporates descriptive statistics, Pearson correlation, and multiple regression models for interpretation and execution of data. Five years (2006-11) panel data of 125 listed companies of Pakistan stock exchange (PSX) is selected in accordance to sample selection criterion. Results of regression analysis supported an inverse relationship between firm`s profitability and working capital management. Return on asset and Gross operation income are taken as indicators of profitability. Inventory turnover in days, Average age of A/R, Average payable period and Cash conversion cycle are considered as independent variables to measure firm’s profitability. Firm size, Sales growth, and financial debt ratio are favored as control variables. Overall Return on asset models indicated poor values of R-square`s and Gross operating income models showed robustness.